A lightweight container-based virtual time system for software-defined network emulation. Issue 3 (1st August 2017) - Yan, Jiaqi; Jin, Dong
Abstract: Container-based network emulation offers high fidelity and a scalable testing environment to bridge the gap between research ideas and real-world network applications. However, containers take their notions of time from the physical system clock, and thus the time-stamped events from different containers are multiplexed to reflect the scheduling serialization by the Linux operating system. Conjoining the emulator and other simulators is also challenging due to the difficulties of synchronizing the virtual simulation clock with the physical system clock. Virtual time systems for network emulation shed light on both issues. In this paper, we develop a lightweight container-based virtual time system in Linux Kernel. We use time dilation to trade time with system resources by precisely scaling the time of interactions between containers and physical devices. We develop a time freezer to enable the precise pause and resume of an emulation experiment, which offers the virtual time support to interface with simulators for close synchronization. We integrate the virtual time system into a software-defined networking emulator, Mininet, and evaluate the system accuracy, scalability, and overhead. Finally, we use the virtual-time-enabled emulation testbed to conduct a case study of equal-cost multi-path routing protocol analysis in a data center network.